Shareholder valuation on a dollar of cash versus agency cost: evidence from high-cash and low-cash level firm - Soh, Wei Ni; Mohd Ashhari, Zariyawati; Muhamad, Haslinah (Human Resource Management Academic Research Society, 2020)
The corporate cash holdings are important when deciding performance and profitability of firms, and also as an extension to shareholders’ wealth. The issue of the amount of cash holdings in firms does not solely impact the firms’ balance sheets and agency costs. This study argues that the need for holding more cash to reduce default probability is relatively more significant, and should be focused upon rather than agency cost. To compare the agency cost and the value of holing more cash in firm, this study employs the Faulkender & Wang (2006) methodology in estimating the cash value against excess stock returns, which reflects shareholders’ valuation. As the findings, firms with higher cash would generate higher excess stock returns. The shareholders’ valuation does not tally with agency cost, showing that shareholders prefer firms to hold less cash. Furthermore, the optimal cash level is not significantly related with shareholders’ valuation.